Characterization of additional zinc ions on the growth, biochemical composition and photosynthetic performance from Spirulina platensis. (December 2018) - Zhou, Ting; Wang, Jingjing; Zheng, Hongli; Wu, Xiaodan; Wang, Yunpu; Liu, Mingzhi; Xiang, Shuyu; Cao, Leipeng; Ruan, Roger; Liu, Yuhuan
Highlights: Zinc contributed to algae fatty acids composition. The maximum Carotenoid content was obtained at low zinc level. Zinc stress inhibited the synthesis of phycocyanin. Spirulina platensis shown the best adsorption capacity in 4.0 mg/L. The effect of zinc ion on photosynthetic performance was discussed. Abstract: In this study, the effect of various initial Zn 2+ concentration additionally on microalgae growth and biochemical composition were investigated. The Spirulina platensis biomass of each concentration reached the maximum at the end of the cultivation. However, high levels could severely inhibit the growth of microalgae. Fluorescence activity occurred changes in response to heavy metal stress. Moreover, biochemical composition in Spirulina platensis altered under zinc stress, and the highest contents of phycocyanin (PC), Chlorophyll- a (Chl- a ), Carotenoid and zinc accumulation were obtained. The proportion of saturated and polyunsaturated fatty acids increased constantly in response to Zn 2+ exposure. Overall, this study indicated that the use of Spirulina platensis is a viable method for treating zinc containing wastewater and harvested microalgae can be processed into high-zinc products.